POLÍMERO ANTIMICROBIANO [QAMP] PARA INCORPORAÇÃO EM SISTEMA ADESIVO ODONTOLÓGICO: DESENVOLVIMENTO, CARACTERIZAÇÃO FÍSICO-QUÍMICA, AVALIAÇÃO DA PERMEABILIDADE VASCULAR E PROPRIEDADES MECÂNICAS - Pupo, Yasmine Mendes (2013)
The use of bioactive restorative materials, with the ability to reduce biofilm development and to present direct action against cariogenic microorganisms, has grown in the dental market and a trend in Adhesive Dentistry. This study aims to describe the synthesis, the characterization, the antimicrobial properties, the vascular permeability and the mechanical properties of the quaternary ammonium methacrylate polymer [QAMP], for incorporation into dental adhesive systems, in order to provide increase the durability of dental restorations. QAMP was obtained through chemical modification (alkylation) of a preformed polymer [Eudragit™ E100] and n-octyl bromide. The resulting product [QAMP] was characterized by infrared spectroscopy, Raman spectroscopy, Nuclear Magnetic Resonance spectroscopy, Visible spectrophotometry, X-ray diffraction and thermogravimetric analysis (TGA). The in vitro susceptibility testing against Streptococcus mutans of QAMP was performed prior and after incorporation into a commercial adhesive system (Clearfil™ SE Bond). Clearfil™ Protect Bond containing antimicrobial standard [MDPB] and Clearfil™ SE Bond without QAMP were used as positive and negative controls, respectively. To evaluate percentage of quaternary ammonium compound released from the experimental adhesive system a test was conducted, after intervals of predetermined time (1, 7, 14, 21 and 30 days). Spectroscopic data confirmed that QAMP was successfully acquired. Thermal analysis indicated that QAMP was heat-stable. The antimicrobial effect against the Streptococcus mutans, prior and after incorporation in a dental adhesive system, was proven. The release of the quaternary ammonium compound [QAMP], embedded in an adhesive system, was reduced when compared to the commercial product [MDPB]. Additionally, the effect of Clearfil™ SE Bond containing QAMP on the vascular permeability using Evans blue and laser!"!Doppler flowmetric methods was investigated in order to define the influence on the exudative phase of the inflammatory process in the subcutaneous tissue of rats. Results support that the adhesive system containing QAMP had lower effect on this phase indicating an adequate biocompatibility. In an attempt to determine the stability of QAMP, the bond strength of adhesive systems was evaluated in extracted human teeth through microtensile test immediately, after 6 and 12 months of storage of the stick-shaped specimens. The degree of conversion of the bonding interfaces was investigated, using micro-Raman spectroscopy, and in vitro by infrared Fourier Transform. Data obtained confirm that a self-etching adhesive system with the quaternary ammonium methacrylate polymer [QAMP] could produce the effective bond strength under in vitro conditions and stability of the degree of conversion in situ and in vitro. In the evaluation of mechanical properties, hardness and elastic modulus, slices of restored teeth were prepared with adhesives under study and were submitted to artificial methods for producing caries lesions during, pH-cycling or microbiological assay, for subsequent nanoindentation test performed in the region of the interface resin-dentin, leading to check the quality of the formed substrate. In general, Clearfil™ SE Bond containing QAMP provided better mechanical properties for the resin-dentin interface than other commercial selfetching adhesives after cariogenic challenges. These data include the development of quaternary ammonium polymers to provide additional benefits for dental adhesive systems widely used in dentistry.